Risk Analysis of Substation Electrical Project - Suwaibah Al Aslamiyah; Hajji, Apif Miptahul; Alfianto, Imam (Rekayasa Sipil, 2024)
The electricity infrastructure project is a complex construction project with many types, activities, and synergies from internal and external stakeholders.  The Gas Insulated Switchgear (GIS) 150kV of Gunungsari is a substation electrical construction project with delays in its construction process. The emergency of delays due to project risks that are not handled properly during the completion process and potentially create new risks. This study aims to identify the risks of project delays and determine effective risk treatment. The risk management process carried out in this study refers to ISO 31000:2018, which starts by defining the scope, context, and risk criteria, then continues with risk assessment, including risk identification, risk analysis, and risk evaluation, and then continues by determining risk treatment. Risk identification was obtained through literature study and Focus Group Discussion (FGD) with expert judgment involved in the project. The risk analysis results using the risk matrix obtained the most dominant risks, such as delays in project handover and additional item construction. The major risks included are those that require risk treatment to reduce the level of risk.